Electronics math - Deem, Bill R. (Prentice-Hall, 1997)
Ideal as a review/reference, this best-seller focuses on mathematical topics that are most useful in solving electronics problems. Hands-on in approach it features an abundance of step-by-step examples, practice problems, and self-tests.Calculator usage is covered as necessary.